VIBES: Visionary Ingenuity Boosting European Spacecraft. Managing microvibrations for the future of spaceflight - Antonio Garcia; Tim Gust; Enes Basata; Tim Gersting; Michal Deka; Sven Thiele; Mohammad Salah; Matias Bestard Koerner; Torben Runte; Miguel Gonzalez (Archive of Mechanical Engineering, 2023)
Microvibrations are mechanical oscillations caused by components such as the reaction wheels of an attitude control system of a spacecraft. These microvibrations are transferred through the spacecraft structure onto important instruments (e.g., optical instruments), causing those to produce diminished results (e.g., reduced image quality, imprecise geolocation etc.). At the present state, microvibrations in spacecraft cannot be actively controlled because their very high frequencies of up to 1000 Hz are above the control bandwidth a current attitude control system can provide. However, being able to reduce the effects of microvibrations on a space mission is becoming increasingly more critical as the envelope of future optical satellite missions expands. Furthermore, the advancements made in the performance of small satellites as well as the growing interest in laser and quantum communication call for a cost-efficient solution for managing microvibrations. This paper describes how cheap MEMS-based measurement systems have already proven that they are a potential solution. Showing high sensitivity and low-noise performance while allowing fast and easy prototyping.